2020
DOI: 10.1177/0309364620968645
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of lower limb loss in children and associated costs of prosthetic devices: A national study of commercial insurance claims

Abstract: Background: Although the incidence of major pediatric lower limb loss secondary to either congenital deficiencies or acquired amputations is relatively low, the prevalence of lower limb loss among children in the United States (US) remains unknown. Objectives: To estimate the prevalence of major lower limb loss, and the associated prosthetic services use and costs among commercially-insured children in the US. Study design: Observational, retrospective, longitudinal cohort study. Methods: The IBM MarketScan® C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…However, literature shows that unilateral upper limb deficiency is the most common congenital limb loss. 7,[9][10][11] Epidemiological studies investigating acquired limb loss in the pediatric population shows that trauma is the most common cause of limb loss. [11][12][13] Similar to congenital limb loss, the prevalence of acquired limb loss differs widely in literature, given the methodological differences in studies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, literature shows that unilateral upper limb deficiency is the most common congenital limb loss. 7,[9][10][11] Epidemiological studies investigating acquired limb loss in the pediatric population shows that trauma is the most common cause of limb loss. [11][12][13] Similar to congenital limb loss, the prevalence of acquired limb loss differs widely in literature, given the methodological differences in studies.…”
Section: Introductionmentioning
confidence: 99%
“…7,[9][10][11] Epidemiological studies investigating acquired limb loss in the pediatric population shows that trauma is the most common cause of limb loss. [11][12][13] Similar to congenital limb loss, the prevalence of acquired limb loss differs widely in literature, given the methodological differences in studies. McDonald et al 12 estimated the global prevalence of traumatic limb amputation based on the "Global Burden of Disease Study 2017" and found that 57.7 million people were living with limb amputation due to traumatic causes worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a prevalence of 38.5 cases per 100,000 per year between 2009-2015. 2 Congenital limb absence or difference accounted for 84% of the cases, followed by trauma at 13.5%. 2 Although this diagnosis may initially be devastating to the family, with care from the multidisciplinary medical team, these children tend to do well.…”
Section: Introductionmentioning
confidence: 99%